PARASITOLOGICAL CONTAMINATION IN ALFACES (Lactuca sativa) COMMERCIALIZED IN CAMPINA GRANDE-PB - Lima, Jailton Lobo da Costa (2020)
Parasitic infections have been a public health problem among developing countries, including Brazil, due to poor sanitation and ingestion of contaminated water and food. Given this, the objective of this work was to analyze the parasitic contamination in lettuce commercialized in the central fair and supermarkets of Campina Grande-PB. Ten samples were collected, five sold in the central fair and five sold in supermarkets in the city. These samples were processed in the Uninassau - CG laboratory, where two leaf washes were performed and the water used in the washes was submitted to spontaneous sedimentation technique for parasite research. After microscopic analysis, contamination was detected in all samples, but the samples from the central fair had a larger variety of parasites. The most prevalent parasitic forms were Endolimax nana (100%), Balantidium coli (90%) and Strongyloides stercoralis (70%). From these results it can be concluded that there is a high contamination of vegetables sold in the city, due to the transportation, packaging and handling of these vegetables, offering risks to the population that consumes them. Demonstrating the need for the hygiene of these vegetables by their consumers, aiming to reduce the number of parasitic infections and improve the quality of life.